Application of the Problem Based Learning (PBL) Learning Model in Increasing Student Participation in Pancasila Education Learning in Classes X-5 of Madani Integrated Model State High School - Rahmawati1, Rahmawati; Etta, Nita Suriyani; Jamaludin, Jamaludin (CV. Rayyan Dwi Bharata, 2025)
The aim of this research is to increase the participation of students in class This research is class action research (Class Action Research) which consists of two cycles. Each cycle consists of action planning, action implementation, observation and reflection. The research subjects were students in class X-5 at SMA Negeri Madani Integrated Model High School. Data sources come from teachers and students obtained through observation, interviews, tests and document review. The data analysis technique used is descriptive analysis. The results of the research show that: (1) The teacher's ability to carry out learning using the problem based learning (PBL) method to improve student learning outcomes in learning Pancasila education in class X-5 in cycle I has an average of 67.5% (quite good) , while in cycle II it was 82.5% (very good), this shows an increase of 15%. (2) The number of students who are active in learning gradually increases in cycle II. This number has met the target that has been set even though at the beginning of the cycle student participation was still far from the target, in fact there were no participants at all.